Sustainable nano-sodium silicate and silver nitrate impregnated locally made ceramic filters for point-of-use water treatments in sub-Sahara African households - Omeje Maxwell (Elsevier, 2021)
The poor access to water quality for Nigerians has pushed for the designing of new trend silver nitrate impregnated locally made Point-Of-Use (POU) ceramic filters to enhance water purification efficiency for household use. This study utilized silver nitrate-molded ceramic filters prepared with Kaolin from Owode, silt soil, sodium silicate, sawdust, and distilled water in three varying proportions to ascertain pollution removal efficiencies. Heating was carried out by firing the filters at 900 °C and further preheating at 400 °C after dipping in silver nitrate solution. Silver nanoparticle and dissociated particle discharge from filter pot painted with 0.03 mg/g casein-covered nAg or AgNO3 were estimated as an element of pH (5–9), ionic strength (1–50mM), and cation species (Na+, Ca2+, Mg2+). Silver delivery was constrained by disintegration as Ag+ and resulting cation exchange measures, paying little heed to silver structure applied. Water analysis for both heavy metals (Pb and Cd) and microbial load (E. coli) evaluated, corroborate the maximum removal efficiency. It was observed that kaolin-sawdust with the Silver nitrate filters showed a constant and effective removal of both heavy metals and disinfection of microbial loads. The minimum flow rates observed were 4.97 mL/min for batch filter used for Iju River water sample one (AF1) and 4.98 mL/min for batch filter used for Iju River water sample two (AF2) having porosity 49.05% and 50.00%, whereas the 5 mL/min higher flow rate was used for batch filter from borehole water sample one (BF1) and batch filter used for well water sample two (CF2) with porosity of 50.00%. Significantly, the results obtained show that the filters are suitable for point-of-use application in both the urban and rural areas of developing countries such as Nigeria